Desenvolvimento de competências leitora e escritora no Ensino Fundamental: práticas pedagógicas e formação docente - Trevisan, Itamar Silvestre (2021)
The most recent results of the assessments performed biennially by the Brazilian Basic Education Assessment National System (SAEB), based on the Basic Education Development Index of the country (IDEB) between 2005 and 2019, indicate the goals set out in the National Education Plan (PNE) have not been achieved. In 2017, the National Common Curricular Base (BNCC) was approved. It is a normative document that guides the curriculum of school education and defines the set of essential learning that students must develop throughout Basic Education, which are prescribed in ten general competences. It consists of the implementation of an educational policy in order to ensure that education is integral and available to all students. In view of this context, the object of this research is delimited: to analyse the pedagogical practices of reading and writing skills carried out by Elementary School teachers and teacher training, considering the writing and reading skills the foundation on which all the other competences are based, in the perspective of proposing interventions to improve teaching quality, considering the rights and duties of students, as subjects in development, for the full exercise of their citizenship. The methodology used is a qualitative approach, based on bibliographic research and documentary analysis, including field research in a public Elementary School. The empirical study had as subjects teachers of Basic and Elementary Education. The theoretical basis is founded in the production of authors recognized for their contributions to scientific knowledge pertinent to the object of this study, such as Philippe Perrenoud; José Gimeno Sacristán; Antoni Zabala; Edgar Morin; Paulo Freire; Nilson José Machado; Terezinha Azerêdo Rios; Ivani Fazenda; Jaume Carbonell; Sara Paín, Miguel Arroyo; Carlos Marcelo Garcia; MauriceTardif; Ingedore Villaça Koch; Mikhail Bakhtin; Luiz Antônio Marcuschi; Lilian Maria Passarelli; Magda Soares; Cipriano Carlos Luckesi. The intended contribution of this study is related to the enhancement of the quality of pedagogical didactic practices in Basic Education, especially in the final years of Elementary School, in conjunction with teachers training